ANALISIS PENERIMAAN PENGGUNA TERHADAP PERPUSTAKAAN DIGITAL DIBACA DI PERPUSTAKAAN DAERAH KABUPATEN DELI SERDANG MENGGUNAKAN TEORI TECNOLOGY ACCEPTANCE MODEL - Ainun, Sri; Fathurrahman, Muslih (Cattleya Darmaya Fortuna, 2025)
This study aims to analyze user acceptance of the DIBACA digital library platform in Deli Serdang Regency using the Technology Acceptance Model (TAM) framework. A descriptive quantitative approach was employed, involving 97 respondents selected through purposive sampling. The research instrument was developed based on five main TAM constructs: perceived usefulness, perceived ease of use, attitude toward use, behavioral intention to use, and actual system use. The results indicate that users generally have a positive perception of the platform’s usefulness and ease of use, particularly in terms of information retrieval and willingness to recommend DIBACA. However, usage intensity and the development of digital habits remain suboptimal, with barriers related to low usage frequency, technical challenges, and limited contribution of the platform to user productivity. The study concludes that DIBACA has been moderately well accepted both cognitively and affectively, but this acceptance is not yet fully reflected in actual usage behavior. Therefore, a more comprehensive strategy involving increased outreach, user training, and the development of relevant features is needed to encourage more consistent and sustainable adoption. These findings provide practical contributions to the development of region-based digital library services and reinforce the applicability of the TAM framework in the context of local public services.